2017
DOI: 10.3765/plsa.v2i0.4090
|View full text |Cite
|
Sign up to set email alerts
|

What is in the neighborhood of a tonal syllable? Evidence from auditory lexical decision in Mandarin Chinese

Abstract: Phonological neighborhood effects have been found in spoken word recognition, word production and phonetic variation (Gahl, Yao, & Johnson, 2012; Luce & Pisoni, 1998; Vitevitch, 2002). Overall, words from dense neighborhoods are harder to recognize but easier to produce. However, most previous studies have focused on English, while evidence suggests that these effects may not generalize cross-linguistically due to language-specific configurations of the lexicon (Michael S Vitevitch & Stamer, 2006, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…When examining homophone neighborhood density, it can be seen that the individual tones were hyper-articulated with a longer duration and a later F0 turning point in syllables with high homophone neighborhood density. To understand the patterns, it may be necessary to employ several models from the literature, namely the Neighborhood Activation Model and the communication-based accounts (e.g., Luce, 1986 ; Goldinger et al, 1989 ; Vitevitch and Sommers, 2003 ; Baus et al, 2008 ; Taler et al, 2010 ; Chen and Mirman, 2012 ; Gahl and Strand, 2016 ; Yao and Sharma, 2017 ; Arutiunian and Lopukhina, 2020 ; Karimi and Diaz, 2020 ). A crucial assumption of the Neighborhood Activation Model (NAM) is that the activation and inhibition of the target words during speech processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examining homophone neighborhood density, it can be seen that the individual tones were hyper-articulated with a longer duration and a later F0 turning point in syllables with high homophone neighborhood density. To understand the patterns, it may be necessary to employ several models from the literature, namely the Neighborhood Activation Model and the communication-based accounts (e.g., Luce, 1986 ; Goldinger et al, 1989 ; Vitevitch and Sommers, 2003 ; Baus et al, 2008 ; Taler et al, 2010 ; Chen and Mirman, 2012 ; Gahl and Strand, 2016 ; Yao and Sharma, 2017 ; Arutiunian and Lopukhina, 2020 ; Karimi and Diaz, 2020 ). A crucial assumption of the Neighborhood Activation Model (NAM) is that the activation and inhibition of the target words during speech processing.…”
Section: Discussionmentioning
confidence: 99%
“…This draws upon evidence from lexical decision tasks, naming reaction times, and familiarity rating. Yao and Sharma (2017) have proposed that in tonal languages, such as Mandarin, to define phonological neighbors by the one-phoneme/tone difference rule: any two syllables that only differ in one phoneme or tone are phonological neighbors. Given the abundant Mandarin homophones (i.e., monosyllabic morphemes with the same segmental syllables and tone), psycholinguistic studies on Chinese spoken word production/recognition often employ the notion of homophone neighbors (e.g., Chen et al, 2009Chen et al, , 2016Wang et al, 2012), including only words that share both segments and tone.…”
Section: Introductionmentioning
confidence: 99%
“…It is defined as the number of words generated by substituting, deleting or adding a single phoneme together with their summed frequency (Greenberg & Jenkins 1964). Even though the stimulus construction process ignored tonal distinctions, they were taken into consideration when searching for lexical neighbours, as previous work has shown that including tonal neighbours in neighbourhood density counts improves the correlation between neighbourhood density and reaction time in lexical decision tasks (Yao & Sharma 2017). For example, the form [ku1] would have [ku3] and [ku4] as its neighbours.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, Yao and Sharma [13] investigated the effects of homophone density using an auditory lexical decision task in Mandarin Chinese. Their findings revealed a facilitatory effect of homophone density on accuracy.…”
Section: Effects Of Homophone Density In Mandarinmentioning
confidence: 99%